Optimizing the Resultativeness of Adapting an Economic Entity to the Conditions of Digitalization - Mottaeva, Angela; Stepanova, Julia; Meshkova, Natalia; Semenova, Galina (European Journal of Sustainable Development, 2021)
The paper discusses theoretical approaches to the concept of resultativeness, considers and substantiates modern approaches to adapting an economic entity to the conditions of digitalization. In this study, a formula for calculating the resultativeness of adaptation was established, taking into account the potential capabilities of an economic entity. On the basis of the proposed formula, possible quantitative values ??of the resultativeness of adapting an economic entity to the conditions of digitalization are studied and their interpretation is provided. The paper reveals the economic essence of the absolute and relative differences between the performance indicators of an economic entity, which describe the result of adaptation to digitalization conditions. The components of adaptation resultativeness and a list of expressions describing them are presented. In the course of the study, the resultativeness of adaptation was determined using two research methods: deductive and inductive ones. Based on the results of the study, an algorithm for finding the optimal value of the resultativeness of adaptation in the context of digitalization and its costs is proposed. This algorithm will allow determining the optimal value of the resultativeness of adaptation in the context of digitalization and its costs, based on the calculation of the quantitative value of the resultativeness of adaptation of the enterprise and a retrospective analysis of the components of the resultativeness and costs of adaptation using the Nelder-Mead simplex method.